OPTIMALISASI PRODUKSI MINYAK MELALUI PENERAPAN TEKNOLOGI EOR DENGAN INJEKSI POLIMER DI LAPANGAN X - Edy Soesanto; Nona Julia Zalfa Nisrina; Puspita Dewi Utami; Rafid Endika; Bagus Hery Refangga (Bajang Institute, 2025)
This research discusses the optimization of oil production through the application of Enhanced Oil Recovery (EOR) technology with polymer injection method in Field X. Given the increasing global energy demand and declining oil production from existing fields, EOR is a solution to maximize the utilization of remaining oil reserves. The polymer injection method is proven to be effective in increasing the viscosity of the distressing fluid, thereby improving the mobility ratio between water and oil, and increasing the oil sweeping efficiency in the reservoir.This study uses document analysis and literature study to evaluate the reservoir characteristics and determine the most suitable EOR method. The results of the analysis show that polymer injection and Alkaline Surfactant Polymer (ASP) injection are the most suitable methods to be applied in X Field. The successful implementation of EOR is expected to not only increase oil production but also provide significant economic benefits. Thus, this study provides recommendations for contractors and the government in formulating policies that support the application of EOR technology effectively and efficiently.